1997
DOI: 10.1590/s0103-06631997000200003
|View full text |Cite
|
Sign up to set email alerts
|

Estudo Da Associação Entre Aleitamento, Hábitos Bucais E Maloclusões

Abstract: A proposta do presente trabalho foi associar a forma de aleitamento com a instalação de hábitos bucais deletérios e conseqüentes maloclusões. Foram examinadas 357 crianças, na faixa etária de 3 a 5 anos, pertencentes a creches e escolas da cidade de Belo Horizonte. Para a obtenção de informações sobre o desenvolvimento das crianças, foram enviados questionários para as mães. Houve um retorno de 289 questionários, sendo avaliadas 289 fichas das crianças participantes. Constatou-se que há associação do aleitamen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
3
76

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(123 citation statements)
references
References 6 publications
4
36
3
76
Order By: Relevance
“…5,16,20 In this study it was observed that 44.6% of children had a history of deleterious sucking habits (Table 2). Similar values are found in the literature.…”
Section: Discussionmentioning
confidence: 62%
“…5,16,20 In this study it was observed that 44.6% of children had a history of deleterious sucking habits (Table 2). Similar values are found in the literature.…”
Section: Discussionmentioning
confidence: 62%
“…Some researches 14,15 shows that the use of nursing nipples is inversely proportional to the exclusive breastfeeding 14 , and that breastfeeding (and consequently baby bottles deprivation) is inversely proportional to negative oral habits ocurrence 15 . However, the nursing nipple, when necessary for reaching emotional stability, must be used rationally, since harmful effects severity is related to duration (period of use), frequency (number of times per day) and intensity (each suction duration and involved muscles activity) used, and may determine dental malocclusion, poor tongue posture and articulatory problems 16 .…”
Section: Discussionmentioning
confidence: 99%
“…The use for a long time period could still be explained by the lack of knowledge from the parents about the deleterious effects of bottle, (e.g dental occlusion). Therefore it justifies conducting effective studies with population focused on breastfeeding as an infant priority to buster the myth of using bottle, specially prolonged use that may affect dental facial development of the child 10,17,19,22 .…”
Section: Discussionmentioning
confidence: 99%
“…The study of Ferreira and Toledo 15 conducted with 427 children aged from three to six years old showed that the longer breastfeeding period is, the lower will be the occurrence of suction habits, mouth breathing and buxism habits. Several studies stated that exclusive breastfeeding for six month will satisfy the suction physiological need of children decreasing nutrition unrelated sucction 4,[16][17][18][19][20][21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation